2008
DOI: 10.1016/j.ejvs.2008.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Is Heparin Reversal with Protamine after Carotid Endarterectomy Dangerous?

Abstract: These results show a non-significant increase in stroke rate in patients receiving heparin alone refuting suggestions that protamine is harmful. Conversely post-operative haematoma was more frequent when protamine was withheld but re-operation rates were no different. Thus protamine use appears safe and should remain a matter for individual surgeon preference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 8 publications
(10 reference statements)
0
33
0
Order By: Relevance
“…13-15 Other literature, including a report from the General Anaesthetic vs Local Anaesthetic for Carotid Surgery (GALA) Trial, has shown conflicting evidence, with reduction in hematoma when using protamine but no differences in reoperation rates. 16-17 …”
Section: Discussionmentioning
confidence: 99%
“…13-15 Other literature, including a report from the General Anaesthetic vs Local Anaesthetic for Carotid Surgery (GALA) Trial, has shown conflicting evidence, with reduction in hematoma when using protamine but no differences in reoperation rates. 16-17 …”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for an adverse reaction are sensitivity to fish (as may occur in traditional fishermen who are often exposed to fish proteins when cutting themselves), a history of vasectomy (which may demolish the blood-testis barrier with consequent formation of anti-semen antibodies) and a history of receiving protamine sulphate containing insulin. Initial reports that the use of protamine sulphate could lead to an increased risk of rebound thrombosis, in particular ischemic stroke [12,13] are not confirmed in a recent randomized controlled study [14].…”
Section: Heparin and Low Molecular Weight (Lmw) Heparinmentioning
confidence: 99%
“…Early studies noted a higher risk of stroke with postoperative protamine reversal, [4][5][6] but subsequent larger studies found no increased risk of stroke with protamine in patients with carotid endarterectomy. [7][8][9][10] Several of these studies reported a benefit to protamine use via reduced risk of bleeding complications. 6,[9][10][11] Protamine use after percutaneous coronary interventions has also been studied extensively.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] Several of these studies reported a benefit to protamine use via reduced risk of bleeding complications. 6,[9][10][11] Protamine use after percutaneous coronary interventions has also been studied extensively. Protamine administration did not predispose to stent thrombosis, 12 myocardial infarction, 13 or coronary restenosis 14 but was found to be associated with reduction in major femoral access site bleeding complications.…”
Section: Discussionmentioning
confidence: 99%